Dead in the water - Johnson, Janice (Janice Kay) (Harlequin intrigue, 2021)
Claire Holland is terrified whan her kayaking adventure accidentally intercepts a smuggling operation and her friend is gunned down. But before she can escape, Claire witnesses someone getting shot and falling overboard. Once she pulls him ashore, she discovers undercover agent Adam Taylor is still alive but badly injured. Now they must navigat the dangerous coatal wilderness unseen. But has Claire save a handsome hero's life...just to find her own in jeopardy?